Outcomes of living donor renal transplantation in children with lower urinary tract dysfunction: a comparative retrospective study. (2nd November 2015) - Saad, Ismail R.; Habib, Enmar; ElSheemy, Mohammed S.; Abdel‐Hakim, Mahmoud; Sheba, Mostafa; Mosleh, Aziz; Salah, Doaa M.; Bazaraa, Hafez; Fadel, Fatina I.; Morsi, Hany A.; Badawy, Hesham
Abstract : Objectives: To compare outcomes of renal transplantation (RTx) in children with end‐stage renal disease (ESRD) resulting from lower urinary tract dysfunction (LUTD) vs other causes. Patients and Methods: A database of children (<18 years old) who underwent RTx between May 2008 and April 2012 was reviewed. Patients were divided into those with LUTD (group A, n = 29) and those with other causes of ESRD (group B, n = 74). RTx was performed after achieving low intravesical pressure (<30 cmH2 O) with adequate bladder capacity and drainage. The groups were compared using Student's t‐ test, Mann–Whitney, chi‐squared or exact tests. Graft survival rates (GSRs) were evaluated using Kaplan–Meier curves and the log‐rank test. Results: The mean ±sd (range) age of the study cohort was 5.05 ± 12.4 (2.2–18) years. Causes of LUTD were posterior urethral valve (PUV; 41.4%), vesico‐ureteric reflux (VUR; 37.9%), neurogenic bladder (10.3%), prune belly syndrome (3.4%), obstructive megaureter (3.4%) and urethral stricture disease (3.4%). There was no significant difference in age, dialysis duration or donor type. In group A, 25 of the 29 patients (86.2%) underwent ≥1 surgery to optimize the urinary tract for allograft. Pretransplant nephrectomy was performed in 15 of the 29 patients (51.7%), PUV ablation in nine patients (31%) and ileocystoplasty in four patients (13.7%). The mean ±sd follow‐up was 4.52 ± 1.55 and 4.07 ± 1.27 years in groups A and B, respectively. There was no significant difference in creatinine and eGFR between the groups at different points of follow‐up. The GSRs at the end of the study were 93.1 and 91.1% in groups A and B, respectively ( P = 1.00). According to Kaplan–Meier survival curves, there was no significant difference in the GSR between the groups using the log‐rank test ( P = 0.503). No graft was lost as a result of urological complications. In group B, one child died from septicaemia. The rate of urinary tract infections was 24 and 12% in groups A and B, respectively, but was not significant. No significant difference was found between the groups with regard to the incidence of post‐transplantation hydronephrosis. Of the 22 patients who had hydronephrosis after transplantation, three were complicated by UTI. Injection of bulking agents was required in two patients for treatment of grade 3 VUR. In the third patient, augmentation cystoplasty was needed. Conclusion: Acceptable graft function, survival and UTI rates can be achieved in children with ESRD attributable to LUTD. Thorough assessment and optimization of LUT, together with close follow‐up, are key for successful RTx.